Adjuvant therapy for cholangiocarcinoma after surgery and prognosis factors for cholangiocarcinoma: A single-center retrospective cohort study - Sun, Zhongquan; Han, Xin; You, Wanlu; Tang, Jinlong; Xu, Juehua; Ye, Binglin; Li, Tengfei; Zhang, Yixin; Chen, Kai; Ding, Yuan; Wang, Weilin (Frontiers in Oncology, 2023)
Background: Cholangiocarcinoma (CCA) is a highly heterogeneous malignant tumor, and more than 60% of patients have recurrence and metastasis after surgery. The efficacy of postoperative adjuvant therapy for CCA remains unclear. This study aimed to explore whether adjuvant therapy benefits patients with CCA and examine the independent prognostic factors for overall survival (OS) and progression-free survival (PFS). Methods: Patients with CCA undergoing surgery were retrospectively enrolled in this study from June 2016 to June 2022. The chi-square test or Fisher exact test was used to analyze the correlation between clinicopathologic characteristics. Survival curves were plotted using the Kaplan-Meier method, and the Cox regression model was used for univariate and multivariate analysis to search for independent prognostic factors. Results: Of the 215 eligible patients, 119 patients received adjuvant therapy, and the other 96 patients did not. The median follow-up was 37.5 months. The median OS of CCA patients with and without adjuvant therapy was 45 and 18 months (P < 0.001), respectively. The median PFS of CCA patients with and without adjuvant therapy was 34 and 8 months (P < 0.001), respectively. The Cox univariate and multivariate regression analysis showed that preoperative aspartate transaminase and carbohydrate antigen 19-9, microvascular invasion, lymph node metastasis, differentiation degree, and adjuvant therapy were independent prognostic factors for OS (all P values < 0.05). Preoperative carbohydrate antigen 125, microvascular invasion, lymph node metastasis, differentiation degree, and adjuvant therapy were independent prognostic factors for PFS (all P values < 0.05). The stratified analysis by TMN stage detected significant differences in the early stages (median OS [mOS]: P = 0.0128; median PFS [mPFS]: P = 0.0209) and advanced stages (mOS and mPFS: both P values < 0.001). Adjuvant therapy was also identified as a significantly favorable prognostic factor for OS and PFS in the early stages and advanced stages. Conclusion: Postoperative adjuvant therapy can improve the prognosis of patients with CCA, even in the early stages and advanced stages. All data suggest that adjuvant therapy should be incorporated into the treatment of CCA in all cases, where appropriate.